SAURON observations of disks in spheroids - Bureau, M; Bacon, R; Emsellem, E; Cappellari, M; Verolme, E; de Zeeuw, P; Copin, Y; Davies, R; McDermid, R; Kuntschner, H; Miller, B; Peletier, R (2002)
The panoramic integral-field spectrograph SAURON is currently being used to map the stellar kinematics, gaseous kinematics, and stellar populations of a large number of early-type galaxies and bulges. Here, we describe SAURON observations of cold stellar disks embedded in spheroids (NGC 3384, NGC 4459, NGC 4526), we illustrate the kinematics and ionization state of large-scale gaseous disks (NGC 4278, NGC 7742), and we show preliminary comparisons of SAURON data with barred galaxy N-body simulations (NGC 3623).